STUDENT LEARNING RESULTS ON ADDING FRACTIONS USING THE REALISTIC MATHEMATICS EDUCATION (RME) APPROACH: AN IMPROVEMENT EFFORT - Wida Rachmiati; M. Rifqi Rijal; Nida Faridah (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
The low understanding of 5th-grade students at SDN Ukirsari on adding fractions became the reason for this research. The issue arises because learning approaches tend to be less student-oriented and do not utilize learning media. The RME (Realistic Mathematic Education) approach is implemented as a corrective action to address this issue. This research is Classroom Action Research (CAR) using the Kemmis and Mc. Taggart model which is characterized by each cycle including 4 stages (planning, acting, observation, reflection). To obtain data on action processes and learning outcomes, observation and test techniques are used. The targets for the success of this research were achieved in cycle II. The results of data analysis on cycle I and II learning outcomes prove that there is an increase in the percentage of students' completion after using the RME approach. Based on data analysis from observations, it can be seen that there has been a change in the quality of the learning process to become student-centered. So, the RME approach succeeded in improving the learning outcomes of 5th-grade students at SDN Ukirsari on the concept of adding fractions and was also able to encourage students to be more active during the learning process.Keywords: RME, Fractions, Elementary school.